2001
DOI: 10.1128/mcb.21.18.6102-6112.2001
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Regulation of Immunoreceptor Signaling by SLP-76-Related Adaptor Clnk and Serine/Threonine Protein Kinase HPK-1

Abstract: Recently, the identification of Clnk, a third member of the SLP-76 family of adaptors expressed exclusively in cytokine-stimulated hemopoietic cells, has been reported by us and by others. Like SLP-76 and Blnk, Clnk was shown to act as a positive regulator of immunoreceptor signaling. Interestingly, however, it did not detectably associate with known binding partners of SLP-76, including Vav, Nck, and GADS. In contrast, it became complexed in activated T cells and myeloid cells with an as yet unknown tyrosine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
53
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 45 publications
0
53
0
Order By: Relevance
“…IP3 triggers the efflux of Ca 2ϩ from endothelial reticulum, leading to the influx of extracellular Ca 2ϩ , whereas DAG activates Protein Kinase C. By phosphorylating PLC␥-1, the Bruton's Tyrosine Kinase of the Tec family BTK plays a critical role in the activation of this phospholipase. SLP76 also associates with Clnk, a cytosolic adapter of the SLP76 family which promotes TCR-dependent activation of T cells (36,37) and FcRI-dependent responses of mast cells (38). Clnk deficiency, however, impaired neither TCR signaling in T cells nor FcRI signaling in mast cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…IP3 triggers the efflux of Ca 2ϩ from endothelial reticulum, leading to the influx of extracellular Ca 2ϩ , whereas DAG activates Protein Kinase C. By phosphorylating PLC␥-1, the Bruton's Tyrosine Kinase of the Tec family BTK plays a critical role in the activation of this phospholipase. SLP76 also associates with Clnk, a cytosolic adapter of the SLP76 family which promotes TCR-dependent activation of T cells (36,37) and FcRI-dependent responses of mast cells (38). Clnk deficiency, however, impaired neither TCR signaling in T cells nor FcRI signaling in mast cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…9,10 HPK1 activation involves binding of cell-specific adaptor proteins, relocation to the plasma membrane, autophosphorylation and transphosphorylation by protein kinase D1. [11][12][13] While a role for HPK1 in the regulation of T-cell apoptosis was already suggested, 14 our recent studies have shown proteolytic processing of HPK1 into HPK1-C in non-apoptotic preactivated primary T cells. 15 In this study, the cleavage product HPK1-C sensitizes towards T-cell receptor-mediated cell death, while full-length HPK1 enables activation and survival of T cells.…”
mentioning
confidence: 99%
“…Following recruitment to the TCR, HPK1 is phosphorylated on tyrosine 379 and binds the SH2 domain of SLP-76, which itself is phosphorylated by HPK1 [15][16][17][18][19]. Subsequent transphosphorylation by PKD1 and autophosphorylation within the kinase domain result in full activation of HPK1 [15], which then regulates different cellular responses including apoptosis, activationinduced cell death and autoimmunity [20][21][22].…”
mentioning
confidence: 99%